PENGELOLAAN SAMPAH DI KOTA SEMARANG UNTUK MENUJU KOTA BERSIH - Hariyanto, Hariyanto (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2014)
This study aimed to: 1) determine how much waste volume which resulted by theSemarang City residents, 2) determine waste management of Semarang City inorder to seize title â€œthe cleanest cityâ€. The method used was descriptivequantitative. Population of this study was 70 families (household) which taken bypurposive random sampling. The results of this research showed that wastevolume resulted was 1000-1500 tonnes per day, with 8-12% increasement peryear. Waste volume was affected by the number of members from each household,economic level, and type of activity. 61.2% was organic waste and the rest wasnon-organic waste. The waste management conducted by transported to landfill(31%), burned or dumped (53%), disposed to river or sewer (15%), andcomposted (1.5%). The community considered that waste problem isgovernment's business, not communityâ€™s business. The waste managementapproach was focused to after waste produced and not been directed to decreasewaste volume before produced.